التفاعل الصفي وعلاقته بالدافعية للتعلم لدي تلاميذ المرحلة الثانوية - حراث عبد القادر (كلية العلوم الاجتماعية, 2020)
تهدف هذه الدراسة إلى الكشف عن عالقة التفاعل الصفي بالدافعية لمتعمم لدى تالميذ السنة األولى ثانوي، حيث اعتمدنا عمى المنهج الوصفي، وشممت عينة الدراسة تالميذ السنة األولى ثانوي بثانوية عبد الحق بن حمودة ببمدية سيرات والية مستغانم، بمغ عددهم )00 )تمميذا من بينهم )32 )ذكرا و)22 )أنثى، لمسنة الدراسية 2012 / 2020 ،وتم االعتماد عمى استبيان لقياس التفاعل الصفي المصمم من طرف الباحث، و مقياس لقياس الدافعية لمتعمم المصمم من طرف أحمد دوقة، ولتحميل النتائج اعتمد الباحث عمى معامل ارتباط بيرسون واختبار تحميل التباين ثنائي االتجاه، وذلك باالعتماد عمى برنامج الرزم اإلحصائية لمعموم االجتماعية spss20 ،وبعد المعالجة والتحميل تو صمت الدراسة إلى النتائج التالية: 1 _هناك عالقة إيجابية بين التفاعل الصفي والدافعية لمتعمم لدى تالميذ السنة األولى ثانوي. 2 _وجود فروق دالة إحصائيا في درجة التفاعل الصفي لدى تالميذ السنة األولى ثانوي تبعا لمتغير الشعبة ولصالح شعبة اآلداب، وتبعا لتفاعل كل من الشعبة والجنس. 3 _عدم وجود فروق دالة إحصائيا في درجة التفاعل الصفي لدى تالميذ السنة األولى ثانوي تبعا لمتغير الجنس. 4 _عدم وجود فروق دالة إحصائيا في درجة الدافعية لمتعمم بين تالميذ السنة األولى ثانوي تعزى لمتغيري الجنس والشعبة والتفاعل بينهما. _ الكممات المفتاحية: التفاعل الصفي_ الدافعية لمتعمم_ تالميذ السنة األولى ثانوي. Abstract : This studyaims to reveal the relationship of classroom interaction and motivation to learnamong first-yearsecondarystudents, as werelied on the descriptive curriculum, and the studysampleincludedstudents of the first year of secondaryschoolatAbdelhak bin Hamouda High School in the municipality of Sirat Mostaganem, whosenumberreached (60) pupils, including (32) (Males and (28) females, for the academicyear 2019/2020, and a questionnaire wasused to measureclassroom interaction designed by the studentwith a short life, and the second to measure the motivation for learningdesigned by Ahmed Duchah, and to analyze the results, the researcherrelied on the Pearson correlation coefficient and the Binary Variance Analysis test. The trend, based on the 20spss statistical packages program for social sciences, and afterprocessing and analysis, the studyreached the followingresults: 1_There is a positive relationshipbetweenclassroom interaction and motivation to learnamong first-yearsecondaryschoolpupils. 2 _The presence of statisticallysignificantdifferences in the degree of class interaction among first-yearsecondaryschoolpupilsaccording to the division variable, and according to the interaction of both the division and the gender. 3_There are no statisticallysignificantdifferences in the degree of class interaction among first-yearsecondaryschoolpupils, according to the gender variable. 4 _There are no statisticallysignificantdifferences in the meandegrees of motivation to learnamongstudents of the first year of secondaryschool due to the sex and division variables and the interaction betweenthem. Keywords: classroom interaction - motivation to learn - first yearsecondaryschoolpupils.
Keywords: التفاعل الصفي؛الدافعية للتعلم؛